Newer treatments for decompensated heart failure: focus on levosimendan - Ferenc Follath (Drug Design, Development and Therapy, 2009)
Ferenc FollathUniversity Hospital Zürich, Steering Group Drug Therapy, Zürich, SwitzerlandAbstract: Acute heart failure (AHF) is a major cause of hospitalizations. Severe dyspnea, pulmonary congestion and low cardiac output with peripheral vasoconstriction and renal hypoperfusion is a main form of clinical presentation. Most patients with acute worsening have a pre-existing decompensated chronic heart failure (ADCHF), but AHF may also occur as a first manifestation of a previously unknown heart disease. Myocardial ischemia, cardiac arrhythmias, non-compliance with medication and infections are frequent precipitating factors. Management of AHF depends on the underlying heart disease and cause of decompensation. In patients with ADCHF vasodilators and iv diuretics are first-line drugs for rapid reduction of dyspnea and congestion. In patients with signs of low cardiac output and oliguria, inotropic agents are also often administered to prevent further deterioration. Beta-adrenergic agents and phosphodiesterase inhibitors correct the hemodynamic disturbance, but may also induce arrhythmias and worsen myocardial ischemia. Inotropic therapy therefore remains controversial. A novel class of drugs, the calcium sensitizers, represent a new therapeutic option. Levosimendan was shown to improve myocardial contractility without increasing oxygen requirements and to produce peripheral and coronary vasodilation. Its therapeutic effects and tolerance have been tested in several trials. The present review focuses on the clinical pharmacology and therapeutic utility of levosimendan in patients with ADCHF.Keywords: acute heart failure, inotropic agents, calcium sensitizers, levosimendan